Pengalaman Guru Bimbingan dan Konseling dalam Menangani Anak Berkebutuhan Khusus - AD, Yahya; Kristika, Siti (Universitas Islam Negeri Raden Intan Lampung, 2015)
Children with special needs are children who have body and mental disorders. In exceptional education or special education of children with disabilities, addressed to children who are deemed to have deviations from the normal average condition of normal children, in terms of physical, mental, or social behavior characteristics, or children different from the general average, because there are problems in the ability to think, sight, hearing, socialization, and moving. This study aims to get an overview of the experience of Teacher Guidance and Counseling in dealing with children with special needs. This research uses phenomenology design with in-depth interview method. The data collected was the result of interviews and field notes analyzed, this research produced 24 themes. The results describe feelings of acceptance, feelings of anger, feelings of depression, and the burden of time. The handling done by the Teacher Guidance and Counseling shows the purpose and type of needs by using a variety of specific methods. Guidance and Counseling Teachers need social support and infrastructure and have used several sources and forms of support during the handling of Children with Special Needs. Environmental responses require Master Bk to modify the ways in which children with special needs both in teaching and learning systems cover various barriers, curricula and teaching materials, problem-solving co-operation, student ratings, flexibility, accountability.